2013
DOI: 10.1186/1475-925x-12-131
|View full text |Cite
|
Sign up to set email alerts
|

Effects of positioning on radiographic measurements of ankle morphology: a computerized tomography-based simulation study

Abstract: BackgroundMeasurements of the morphology of the ankle joint, performed mostly for surgical planning of total ankle arthroplasty and for collecting data for total ankle prosthesis design, are often made on planar radiographs, and therefore can be very sensitive to the positioning of the joint during imaging. The current study aimed to compare ankle morphological measurements using CT-generated 2D images with gold standard values obtained from 3D CT data; to determine the sensitivity of the 2D measurements to ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…However, subjective evaluation might contribute to distorted results. Other authors [ 16 ] showed that ankle morphological measurements are very sensitive to the positioning of the joint during imaging.…”
Section: Discussionmentioning
confidence: 99%
“…However, subjective evaluation might contribute to distorted results. Other authors [ 16 ] showed that ankle morphological measurements are very sensitive to the positioning of the joint during imaging.…”
Section: Discussionmentioning
confidence: 99%
“…The conformity of the TAA design to the bone morphology, including proper sizing of the components, is an important factor for the prosthesis to replicate the function of the ankle joint [ 8 ]. Using implants of sizes and shapes precisely matching the osteotomies is expected to be of value for the long-term fixation of the implants [ 13 , 19 , 20 ], and can substantially reduce complications and increase survival rates [ 12 14 ]. Therefore, errors in the measurement of the patient-specific morphological parameters may have critical effects on the pre-surgical decision-making in TAA, including the selection of the size of the implants.…”
Section: Introductionmentioning
confidence: 99%
“…These can also be used for estimating patient-specific morphological parameters and for selecting the size of the prosthesis, particularly owing to their convenience, low cost, and low radiation dose compared with other modalities such as Magnetic Resonance Imaging or Computerized Tomography (CT) [ 21 ]. However, since planar radiographs are two-dimensional (2D) projective images, bones at different distances from the projection plane produce bone images of different size, position and intensity, critically affecting the measurement accuracy [ 19 ]. In addition, the intrinsic articular surfaces of the ankle joint are not symmetrical, and are often oblique with respect to the anatomical planes of the shank and foot.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the centre of the incident X-ray beam does not coincide with the target joint, detected JSW in the projected image contains perceptional or measured errors caused by bony overlap resulting from the oblique incidence of the X-rays. 14,15 Although this phenomenon is unavoidable clinically, to the best of our knowledge, the assessment of the effects caused by the oblique incidence of Xrays has not yet been performed. We therefore performed an assessment using phantoms simulating joints for radiography and tomosynthesis.…”
Section: Introductionmentioning
confidence: 99%